2001
DOI: 10.1021/ic0109389
|View full text |Cite
|
Sign up to set email alerts
|

Early Transition Metal Complexes Containing 1,2,4-Triazolato and Tetrazolato Ligands:  Synthesis, Structure, and Molecular Orbital Studies

Abstract: Several early transition metal complexes bearing 1,2,4-triazolato and tetrazolato ligands have been prepared by reaction of the pyrazolato complexes Ti(tBu(2)pz)(4-x)Cl(x) (tBu(2)pz = 3,5-di-tert-butylpyrazolato; x = 1, 2) and M(tBu(2)pz)(5-x)Cl(x) (M = Nb, Ta: x = 2, 3) with the sodium or potassium salts derived from 1,2,4-triazoles and tetrazoles. The X-ray structure analysis of Ti(tBu(2)pz)(2)(Me(2)C(2)N(3))(2) shows eta(2)-coordination of the 1,2,4-triazolato ligands, while in Ti(tBu(2)pz)(3)(C(2)H(2)N(3))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 115 publications
2
37
0
2
Order By: Relevance
“…Theoretical results demonstrate that particularly in early transition metal compounds there is a strong thermodynamic preference for this kind of coordination over the η 1 -mode. [198] In order to obtain discrete mononuclear complexes with (slipped) η 2 -bonded tetrazoles/tetrazolates, bulky ancillary ligands are required in the coordination sphere as, for instance, in [K(18-crown-6)](η 2 (N 1 ,N 2 )-N 4 CR) (R = Ph, pyrrolidinyl, Bu t ), [199] or in [Ba (18- [198] For the most part, however, coordinative saturation both in simple binary compounds and in the realm of tetrazole-based metal-organic coordination polymers (MOCPs) (see particularly section 1.3. ), is achieved by tetrazolato bridge formation.…”
Section: Tetrazolato Metal Complexes: Coordination Modes Isomerism mentioning
confidence: 99%
“…Theoretical results demonstrate that particularly in early transition metal compounds there is a strong thermodynamic preference for this kind of coordination over the η 1 -mode. [198] In order to obtain discrete mononuclear complexes with (slipped) η 2 -bonded tetrazoles/tetrazolates, bulky ancillary ligands are required in the coordination sphere as, for instance, in [K(18-crown-6)](η 2 (N 1 ,N 2 )-N 4 CR) (R = Ph, pyrrolidinyl, Bu t ), [199] or in [Ba (18- [198] For the most part, however, coordinative saturation both in simple binary compounds and in the realm of tetrazole-based metal-organic coordination polymers (MOCPs) (see particularly section 1.3. ), is achieved by tetrazolato bridge formation.…”
Section: Tetrazolato Metal Complexes: Coordination Modes Isomerism mentioning
confidence: 99%
“…We have previously reported that treatment of group 4 and 5 metal chlorides with potassium pyrazolato salts constitutes an excellent synthetic route to the corresponding group 4 and 5 pyrazolato complexes. [12,13] Accordingly, salt metathesis routes to hafnium pyrazolato complexes were explored. Treatment of hafnium tetrachloride with 4 equiv.…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…[10c, 11,12] Meyer and co-workers reported a homoleptic zirconium complex with four bulky η 2 -pyrazolato ligands. [11] We have reported the synthesis and structure of several zirconium and hafnium complexes that contain pyrazolato ligands, [12] but have not published any structural studies of the homoleptic pyrazolato complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis, structure and thermokinetic studies on perchlorate salts of metal complexes containing a formamidine-type ligand 1…”
mentioning
confidence: 99%